Sentiment Analysis of Government Policy in Relocating the Republic of Indonesia's Capital City - Resti Amelia (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
The policy regarding the relocation of the national capital is a top-down government policy. The public reacted in a variety of ways, both positively and negatively, to this policy. Sentiment analysis is used to determine if someone's opinions and the trend of those opinions on a topic or object are positive, negative, or neutral. The goal of sentiment analysis on the government's plans for moving the capital city is to determine public sentiment through social media and mainstream media using the crawling approach and an external analysis point of view so that these policies may be tested in the eyes of the people. Furthermore, this document makes policy suggestions to the government. The keywords